Pediatric acute lymphoblastic leukemia treatment protocols improvement: emphasis on minimal residual disease - M. A. Shervashidze; T. T. Valiev (Онкогематология, 2020)
Treatment of acute lymphoblastic leukemia (ALL) in children during the last 50 years has changed significantly, which has increased the survival of patients from 10–15 % in the early 60s to 80–85 % by the mid-2000s. Such results have been achieved through the development of new polychemotherapy regimens, the introduction of neuroleukemia prophylaxis, the strengthening of standard chemotherapy by increasing the dose and / or frequency of chemotherapeutic drugs administration, and the definition of criteria for patient stratification into prognostic risks groups and the development of principles of risk-adopted therapy.However, inspite of the overall success of pediatric acute lymphoblastic leukemia therapy, some variants of acute lymphoblastic leukemia associated with poor prognosis, especially acute lymphoblastic leukemia with BCR-ABL1 and MLL rearrangements. Besides the prolonged persistence of minimal residual disease is also an unfavorable prognostic factor requiring therapy intensification.In the current issue we present the main steps in the evolution of programmed chemotherapy of children with acute lymphoblastic leukemia. Great attention was paid for modern risk-stratifying criteria with an emphasis on minimal residual disease.